Proprioceptive training methods (PTM) in female soccer players - a systematic review - Stankovic, M.; Capric, I.; Katanic, B.; Špirtovic, O.; Maljanovic, D.; Nailovic, H.; Mukovic, I.; Jelaska, I.; Trajkovic, N. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Although previous studies have reported that proprioceptive training methods (PTM) have positive effects, there is a relatively small number of studies regarding the impact of PTM in women`s soccer. Therefore, there is a need to systematize the given results. In this regard, this systematic review aimed to investigate the effect of proprioceptive training methods in female soccer players.